Simulation of Ad Hoc On-Demand Distance Vector Routing Protocol in Mobile Ad Hoc Networks - Rahmadani; Silaban, Indra Marto; Safriadi, Safriadi (Indonesian Journal of Science, Technology and Humanities, 2024)
To simulate using a simulator made with a programming language and test the mobile ad hoc network system in the process of sending packets from the source node to the destination node in order to evaluate the stability of the routing protocol used. This research uses the Ad Hoc On-Demand Distance Vector (AODV) protocol which is expected to reduce the processing time (overhead) that often occurs in mobile ad hoc networks, because the routing table is not exchanged between nodes during the ad hoc mode process is taking place in the mobile ad hoc network so that it will speed up the packet delivery process. Tests were carried out by determining the number of different nodes and increasing starting from 5, 15, 25, 35 and 50 nodes, with a bandwidth of 2 Mbps, 1 Mbps packets and an area of 10x10 m2, then running the simulation process with a simulator with the Ad Hoc On-Demand Distance Vector (AODV) protocol. The test results show that the performance metric values on throughput and delay have good and stable performance in the mobile ad hoc network area